PENGASUHAN ANAK USIA DINI PERSPEKTIF NILAI BUDAYA PADA KELUARGA BAJO DI KABUPATEN BONE - Musi, Muhammad Akil; Amal, Azizah; Hajerah, Hajerah (Universitas Negeri Makassar, 2015)
This study aimed to determine the approach to the cultural values of parenting and early childhood education in the family environment. The study was conducted in the form of a case study by focusing on the care of children in a family environment. Data was collected through observation participation, focused interviews, and documentation of archival footage. Selanjutnyan data obtained were analyzed using the dominant models and time series analysis. The results showed that the Bajo family still adhere to a number of cultural values and parenting education as a value which is considered essential to preserve and implanted in a family environment.